2020
DOI: 10.1111/bjh.17231
|View full text |Cite
|
Sign up to set email alerts
|

The expression levels of long non‐coding RNA KIAA0125 are associated with distinct clinical and biological features in myelodysplastic syndromes

Abstract: Summary Long non‐coding RNAs (lncRNAs) have important functions in cancer biology. Among them, lncRNA KIAA0125 is one of the genes proposed to play a critical role in leukaemia stem cell (LSC). In this study, we aimed to investigate the clinical relevance of the expression levels of lncRNA KIAA0125 in myelodysplastic syndromes (MDS), a disease with highly heterogeneous clinical and biological features. Using RNA arrays, we measured the expression of KIAA0125 in 176 primary MDS patients. We found that higher KI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…The expression of lncRNAs was heterogeneous in stMDS throughout the patients, but we observed a greater uniformity and mainly upregulation in lncRNA expression in prMDS (Figure S11). In accordance with previously described lncRNAs with prognostic significance in MDS, [22][23][24] we observed upregulation of MEG3 and KIAA0125 and downregulation of TCL6 in prMDS. Multiple other lncRNAs upregulated in prMDS compared to stMDS have a known function in cancer (Table S4B).…”
Section: Aberrant Splicing and Lncrna Expression Are Increased In Prm...supporting
confidence: 92%
See 1 more Smart Citation
“…The expression of lncRNAs was heterogeneous in stMDS throughout the patients, but we observed a greater uniformity and mainly upregulation in lncRNA expression in prMDS (Figure S11). In accordance with previously described lncRNAs with prognostic significance in MDS, [22][23][24] we observed upregulation of MEG3 and KIAA0125 and downregulation of TCL6 in prMDS. Multiple other lncRNAs upregulated in prMDS compared to stMDS have a known function in cancer (Table S4B).…”
Section: Aberrant Splicing and Lncrna Expression Are Increased In Prm...supporting
confidence: 92%
“…most significantly upregulated lncRNA in prMDS was KIAA0125; its higher expression has previously been associated with concordant upregulation of HSC-associated genes at higher-risk MDS and has emerged as an independent unfavorable prognostic marker for OS and LFS in MDS. 22 Indeed, lncRNAs belong to important epigenetic regulators of tumor-promoting and tumor-restraining pathways and contribute to the regulation of expression of multiple oncogenes and tumor-suppressor genes. 47 Because epigenetic silencing of DDR genes and pathways is a common cause of DDR deficiency in cancer, 38 we correlated two of the significantly overexpressed oncogenic lncRNAs in prMDS, LINC00340 (CASC15) and MALAT1, with their potentially interacting components of DDR pathway (ZEB1 and CDKN1A in the case of LINC00340, and PARP1…”
Section: Discussionmentioning
confidence: 99%
“…Our bioinformatic analyses revealed the significant correlation between high immune cell risk scores and LSC signatures, NF-κB signaling, and oxidative stress characteristics. Recent studies have shown that LSC signatures are associated with higher risk of disease progression and mortality in MDS patients and can serve as prognostic markers independent of R-IPSS risk and genomic alterations 48,49 . Constitutive activation of NF-κB signaling has been known to play a critical role in MDS pathophysiology and as a feature of high-risk MDS 7,8,[50][51][52][53][54] .…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the skewed T cell repertoire in MDS, pathway analysis of differentially expressed genes between patients with the highest and lowest lncRNA risk scores determined T cell-related pathways [e.g., cytotoxic T-lymphocyte-associated protein 4 signaling in cytotoxic T lymphocytes and CD28 signaling in T helper (Th) cells] to be the most significant (60). Hung et al (63) recently identified an association between higher KIAA0125 expression (BM mononuclear cells) and high-risk MDS, ASXL1 and NRAS mutations, and poorer OS and leukemia-free survival. A recent study by Li et al (64) reported an association between a higher expression level of LOC101928834 and a higher white blood cell count, a higher blast percentage, RAEB subtype and a shorter OS time in MDS.…”
Section: Dysregulation Of Non-coding Rna (Ncrna)mentioning
confidence: 99%